Abdominal CT scan findings of a child with hepatic fascioliasis: A case report on rarely reported emerging disease - Mesay Tilahun; Leul Adane; Gashaw Arega; Melkamu Tilahun (Radiology Case Reports)
Fasciolosis is a zoonotic infection caused by trematodes fasciola hepatica and fasciola gigantic, and humans are incidental hosts. Although infrequently reported in developed nations, it is common in developing countries. Few cases have been reported in Africa, specifically in Ethiopia. This article reports a case of a 4-year-old Ethiopian child who presented with right upper quadrant abdominal pain. His complete blood count showed eosinophilia, and imaging demonstrated lesions at peripheral subcapsular parenchyma and central along the biliary tree. Serologic tests confirmed liver fluke infection with fasciola hepatica indirect hemagglutination test titer of 1/4000. Computed tomography imaging appearances of hepatic fasciolosis depend on the phase and course of the disease and should be considered in differential diagnosis of lesions along the biliary tree.